TYPOLOGIZATION OF ESCAPISTS UTOPIAS OF E. SHATSKIY - Черноног, Р. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The position of the famous philosopher and sociologist of the XX century E. Shatskiy concerning the introduction of a policonstructive principle of utopia typologization has been analysed in the article.